Pengaruh pemberian abu sekam padi sebagai bahan desikan pada penyimpanan benih terhadap daya tumbuh dan pertumbuhan bibit kakao (The effects of rice husk ash as desiccation material of seed storage on viability and cocoa seedling growth). - Pudji Rahardjo (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2012)
Rice husk ash as desiccation material can be used to maintain seed viability in storage through its ability to absorb humidity during its storage. High relative humidity caused seed moisture content to increase so the respiration rate of seed increases and uses faster food stock. Finally the viability of seed is lost. A research on use of rice husk ash as desiccation material of cocoa seed storage was conducted in Agronomy Laboratory and Kaliwining Experimental Station, Indonesian Coffee and Cocoa Research Institute. Completely Randomized Design was used in this research with treatment of rice husk ash application on cocoa seed as follows: 0 g/100 seeds (A), 5 g/100 seeds (B), 10 g/100 seeds (C), 15 g/100 seeds (D), and 20 g/100 seeds (E). This experiment used four replications. Cocoa seeds were stored in plastic bag within carton box in ambient temperature. The storage periods were 1, 2, and 3 weeks, and parameters of observation consisted of electrical conductivity of dipped water of cocoa seeds, percentage of seed germination, percentage of seed emergence, early growth parameters at one month old including seedlings height of seedling, diameter, leaf number, root length, and dry weight. The result of the experiment showed that the use of rice husk ash at 5-10 g/100 seeds could maintain electrical conductivity of dipped water at low level, percentage of seed germination at 99-100 % and percentage of seed emergence at 79-91% after two weeks storage. The use of rice husk ash at 5-10 g/100 seeds after two weeks storage affected height of cacao seedling, but did not affected stem diameters, leaf numbers, root lengths, and dry weights